SOX9 Up-Regulation Can Change Survival and Anticancer Resistance in Different Cancer Type - Al-Saadi, Namariq; Al-hraishawi, Husam (Journal of Biomedicine and Biochemistry, 2023)
Background Y-box member SOX9 determines sex. This family’s eight subgroups (A–H) have one to three members each. Sox gene transcription factors are critical for development and conserved across species. Several studies have shown that a tiny percentage of malignant cells, called cancer stem-like cells (CSCs) or tumor-initiating cells, have stem cell traits such self-renewal and differentiation. Self-renewal is thought to cause tumor growth and progression. Mechanistic studies show that SOX9 controls cancer-specific gene networks that are involved in self-renewal, differentia- tion, and extracellular matrix/cytoskeleton remodeling.Objective This review examines SOX9 as a predictive biomarker and its function in cancer beginnings, progression, and therapeutic resistance across many cancer types. This review discusses genetic/epigenetic SOX9 deregulation in several cancers.Results Multiple cancer types revealed high SOX9 expression and prog- nosis in the CBIOportal database. SOX9-targeting small molecules may diminish chemotherapy resistance. Finally, SOX9 over-expression, malig- nant prognosis, and resistance need additional study.